Electrocoagulation technique for removal of COD and turbidity to improve wastewater quality - Ni'am, Moh Faiqun (Tall Oaks Publishing Inc., 2008)
There are wide range of wastewater treatment techniques emerging which include biological processes and physical-chemical processes and physical-chemical processes. It also includes techniques based on electrochemical technology which include electrocoagulation (EC), electroflotation (EF), electrodeposition (ED), electrooxidation (EO), and many others. However, EC has reached profitable commercialization. The EC has been used for the treatment of wastewater by various authors, and is an efficient treatment process for different wastes. It is also an effective process for the destabilization of finely dispersed particles by removing hydrocarbons, greases, suspended solids, and heavy metals from different types of wastewater. The EC is also used for the removal of chemical oxygen demand (COD) and turbidity to improve wastewater quality.